Educational Research Practice in Southern Contexts Recentring, Reframing and Reimagining Methodological Canons (Taylor & Francis, 2024)
Bringing together a unique collection of 18 insightful and innovative internationally focused articles, Educational Research Practice in Southern Contexts offers reflections, case studies, and critically, research methods and processes designed to decentre, reframe, and reimagine educational research in ways that question existing approaches and operationalise the tenets of decolonising theory. This anthology represents a valuable teaching resource with which to challenge the conventional canons of educational research theory and practice. It provides readers with the chance to read high quality examples of research that critique current ways of doing research and to reflect on how research methods can contribute to the project of decolonising knowledge production in and about education in, for example, Africa, South Asia, Asia and Latin America. It grapples with everyday dilemmas and tricky ethical questions about protection, consent, voice, cultural sensitivity and validation, by engaging with real-world situations and increasing the potential for innovation and new collaborations. Educational Research Practice in Southern Contexts will be essential reading for anyone teaching educational research methods and will encourage novice and experienced researchers to rethink their research approaches, disentangle the local and global, and challenge those research rituals, codes and field work practices which are often unproblematically assumed to be universally relevant.
English
Keywords: Education; Educational strategies & policy; Sharlene Swartz, Nidhi Singal, Madeleine Arnot, research methods, educational research methods, research methods in education, Global South, southern contexts, decolonization, decolonizing education